Determinants of Accounting Fraud on the State Civil Apparatus Ministry of Religion in Padangsidimpuan City - Ananda Anugrah Nasution (Universitas Muhammadiyah Surabaya, 2023)
This study was conducted to determine whether the effectiveness of internal control has a significant adverse effect on the tendency of accounting fraud; whether Organizational Culture has a significant negative impact on the Trend of Accounting Fraud, and whether Compliance with Accounting Rules has a significant negative effect on the Trend of Accounting Fraud. This study uses an associative quantitative approach. The population of this research is the entire work unit of the Ministry of Religion throughout the city of Padangsidimpuan. Sampling using the saturated sample technique. Respondents used as samples were the Expenditure Treasurer, Commitment Making Officer, and Budget User Authority, as many as 42 samples. Questionnaires were distributed directly to the State Civil Apparatus who worked in the Satker of the Ministry of Religion in Padangsidimpuan City to obtain the required data. This research uses the Smart PLS application to use the Structural Equation Modeling (SEM) data analysis with Partial Least Square (PLS) model. The evaluation test of the model using the Outer Model Test consists of a discriminant and convergent validity test as a prerequisite test and an Inner Model test as a hypothesis test. The results of this study indicate that the effectiveness of internal control has a significant adverse effect on the tendency of accounting fraud; Organizational Culture has a significant negative impact on the Trend of Accounting Fraud, and Compliance with Accounting Rules has a significant adverse effect on the Trend of Accounting Fraud